2016
DOI: 10.1177/0305735616671408
|View full text |Cite
|
Sign up to set email alerts
|

Long-term representations of melodies in Western listeners: Influences of familiarity, musical expertise, tempo and structure

Abstract: We investigated the effects of familiarity, level of musical expertise, musical tempo, and structural boundaries on the identification of familiar and unfamiliar tunes. Healthy Western listeners (N = 62; age range 14–64 years) judged their level of familiarity with a preselected set of melodies when the number of tones of a given melody was increased from trial to trial according to the so-called gating paradigm. The number of tones served as one dependent measure. The second dependent measure was the physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Five papers required an additional practice time criterion. Of these, two papers required at least an hour of practice per week (Büdenbender & Kreutz, 2016, 2017); one paper required at least once a week of practice (Taylor & Dewhurst, 2017); one paper required at least 2.5 hours of practice per week (Weijkamp & Sadakata, 2017); and one reported “regular” practice (Castro & Lima, 2014). An analysis of the practice time criterion can be found in the “Weekly practice time” section below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five papers required an additional practice time criterion. Of these, two papers required at least an hour of practice per week (Büdenbender & Kreutz, 2016, 2017); one paper required at least once a week of practice (Taylor & Dewhurst, 2017); one paper required at least 2.5 hours of practice per week (Weijkamp & Sadakata, 2017); and one reported “regular” practice (Castro & Lima, 2014). An analysis of the practice time criterion can be found in the “Weekly practice time” section below.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that only a portion of papers detailed the musicians’ self-reported hours of practice (26% of total papers; 10 out of 39). Of these, five papers reported a minimum number of practice hours per week to allow membership of the musician category (Büdenbender & Kreutz, 2016, 2017; Habibi et al, 2013; Marozeau et al, 2013; Weijkamp & Sadakata, 2017); four papers detailed an average number of practice hours per week (Castro & Lima, 2014; Proverbio & Orlandi, 2016; Sears et al, 2014; Woolhouse et al, 2016); and one paper reported “at least once a week” of practice (Taylor & Dewhurst, 2017). Four papers that reported an average of practice hours had a median of 13.9 hours of practice per week, while five papers reported a minimum of one hour of practice per week.…”
Section: Resultsmentioning
confidence: 99%
“…Famous melodies are also a useful stimulus for investigating the timing of melody recognition (Bailes, 2010). For example, prior work indicates that individuals can recognize musical melodies within 500 ms or a few notes (Büdenbender & Kreutz, 2016;Dalla Bella, Peretz, & Aronoff, 2003;Filipic, Tillmann, & Bigand, 2010;Huijgen et al, 2015;Tillmann, Albouy, Caclin, & Bigand, 2014). Familiar melodies are also a frequently used stimulus for evoking autobiographical memories (Belfi, Karlan, & Tranel, 2016;Ford, Addis, & Giovanello, 2011;Janata, Tomic, & Rakowski, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies of long-term memory for songs have revealed that cultural aspects (e.g., the origin and popularity of a given tune) and their functional meaning in every-day practices (e.g., celebrations, festivities, rituals) can influence their mental representations along with their structural complexity (Büdenbender and Kreutz, 2015 , 2017 ). Songs that were developed for specific purposes such as foreign or second language learning must also be acknowledged for potentially different levels of meaning beyond their surface structures (melody and rhythm) and associated linguistic content (lyrics).…”
Section: Discussionmentioning
confidence: 99%